THE SITUATION OF IMPLEMENTATION OF THE NATIONAL IMMUNIZATION INFORMATION MANAGEMENT SYSTEM IN PHU YEN PROVINCE IN 2021 - Nguyen Thị Thang; Tran Ngoc Than; Le Thuy Phuong; Nguyen Thi Thanh Van; Luong Thi Khuyen (JOURNAL OF CONTROL VACCINES AND BIOLOGICALS, 2023)
The National Immunization Information Management System is a technological innovation management tool that enhances the performance of managers and health professionals in the evaluation and monitoring of immunization activities. However, until now it still faces challenges regarding its operation and use, impacting on its results. To evaluate the current status of implementing the national immunization information management system in Phu Yen in 2021. Cross-sectional study. Most vaccination facilities have stable electricity and internet (98,3%). However, the number of facilities with barcode scanners is still low (34,2%). 91,7% of the staﬀ are relatively good at using NIIS. 83,3% of medical facilities input data according to the right process after the vaccination session. There is a need to strengthen monitoring of support and training for health workers as well as proactively control data on their System on a regular basis.